TEACHING GRAMMAR FOR ACTIVE USE: A FRAMEWORK FOR COMPARISON OF THREE INSTRUCTIONAL TECHNIQUES - Sasan Baleghizadeh (TEFLIN, 2011)
Abstract: Teaching grammar in a way that enables students to use grammatical structures correctly in their active use has always been one of the intricate tasks for most practitioners. This study compared the efÂfectiveness of three instructional methods: games, dialogues practiced through role-play, and unfocused tasks for teaching grammar. Forty eight pre-intermediate female students participated in this study. The structures chosen were Conditional Sentence Type 2 and Wish structures for expressing present desires. A posttest was administered to assess the subjects productive knowledge of the grammatical patterns. The results showed that there were no significant differences in the performance of groups. In other words, all three methods were equally effective to boost students grammatical knowledge of the two structures.